2016
DOI: 10.5114/jcb.2016.61703
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of image-guided brachytherapy (IGBT) for patients with uterine cervix cancer: a tumor volume kinetics approach

Abstract: PurposeTo evaluate tumor shrinking kinetics in order to implement image-guided brachytherapy (IGBT) for the treatment of patients with cervix cancer.Material and methodsThis study has prospectively evaluated tumor shrinking kinetics of thirteen patients with uterine cervix cancer treated with combined chemoradiation. Four high dose rate brachytherapy fractions were delivered during the course of pelvic external beam radiation therapy (EBRT). Magnetic resonance imaging (MRI) exams were acquired at diagnosis (D)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 27 publications
0
8
0
2
Order By: Relevance
“…It is worth pointing out that since the constraint was always met for the rectum and the sigmoid, the limiting value of EQD 2 was higher than the value in the previous fraction. The cumulative EQD 2 combining EBRT and brachytherapy for the bladder in this case was 85.4 Gy < 90 Gy, and for the rectum and sigmoid at 62.2 Gy < 75 Gy and 53 Gy < 75 Gy, respectively, thereby meeting all the OARs constraints recommended [14,15,16,19,27,28]. The increase in applicator angle in this case, however, was not found to increase D 2cc to the rectum and sigmoid.…”
Section: Example Case 1: Meeting the Bladder Constraint By Adjusting mentioning
confidence: 83%
“…It is worth pointing out that since the constraint was always met for the rectum and the sigmoid, the limiting value of EQD 2 was higher than the value in the previous fraction. The cumulative EQD 2 combining EBRT and brachytherapy for the bladder in this case was 85.4 Gy < 90 Gy, and for the rectum and sigmoid at 62.2 Gy < 75 Gy and 53 Gy < 75 Gy, respectively, thereby meeting all the OARs constraints recommended [14,15,16,19,27,28]. The increase in applicator angle in this case, however, was not found to increase D 2cc to the rectum and sigmoid.…”
Section: Example Case 1: Meeting the Bladder Constraint By Adjusting mentioning
confidence: 83%
“…Nevertheless, it was possible to achieve the suggested doses both in HR-CTV and OAR according to the GEC-ESTRO guidelines. In a recent study, it was shown that during the definitive radiotherapy for cervical cancer patients, the most expressive tumor shrinking occurs in the first three weeks of oncological treatment [ 20 ]. Platta et al started BRT application following 23 rd fraction of EPRT in order to complete the treatment within the recommended duration [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, if such displacement occurs intra-fractionally, one should expect dose variation of similar magnitude as well as shown by some recent studies [ 15 , 16 ]. Some studies have looked into the geometric displacement, anatomic change, and other effect in each fraction of image-guided brachytherapy [ 17 , 18 , 19 , 20 , 21 ]. Monitoring of applicator motion relative to patient is therefore important in MR/CT-guided HDR brachytherapy.…”
Section: Purposementioning
confidence: 99%